Computer Sales Forecasting System Application Using Web-Based Single Moving Average Method - Permatahati, Ita; Muqorobin, Muqorobin (International Journal of Computer and Information System (IJCIS), 2022)
Abstract—Hamas Com Computer Store is one of the computer shops in the city of Surakarta. There is a change in the turnover of toy sales every year, management management in managing the store's financial statements. hence the need for a system that can forecast sales of goods for the coming year. The purpose of this research is to design a computer goods sales forecasting system by applying the Single Moving Average method. This method was chosen because it has the ability to observe, look for the average value as a forecast for the future period. Data collection techniques in this research are observation (observation), interviews (interviews) and literature study. In the design of this system is made with Context Diagram, HIPO, DAD, relations between tables, database design and UML. This application is made using the PHP programming language and the database uses MySQL. The final result is a sales data report and sales prediction results. The results of the tracking signal control chart error test results show a value of no more than 4 so the system is declared good.